2010
DOI: 10.1158/1541-7786.mcr-10-0090
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Nonapoptotic Cell Death by Activated Ras Requires Inverse Regulation of Rac1 and Arf6

Abstract: Methuosis is a unique form of nonapoptotic cell death triggered by alterations in the trafficking of clathrinindependent endosomes, ultimately leading to extreme vacuolization and rupture of the cell. Methuosis can be induced in glioblastoma cells by expression of constitutively active Ras. This study identifies the small GTPases, Rac1 and Arf6, and the Arf6 GTPase-activating protein, GIT1, as key downstream components of the signaling pathway underlying Ras-induced methuosis. The extent to which graded expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 79 publications
7
97
2
Order By: Relevance
“…Under normal conditions where the macropinosome matures and is then recycled back up to the cell membrane, activation of Arf6 is again required for this final step and membrane fusion (54,78). In U251 cells, the resting activity of Arf6 is high but drops significantly upon stimulation of macropinocytosis (23). In contrast to these results, we observed no change in the activation levels of Arf6 in NGF-stimulated Daoy-TrkA cells.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…Under normal conditions where the macropinosome matures and is then recycled back up to the cell membrane, activation of Arf6 is again required for this final step and membrane fusion (54,78). In U251 cells, the resting activity of Arf6 is high but drops significantly upon stimulation of macropinocytosis (23). In contrast to these results, we observed no change in the activation levels of Arf6 in NGF-stimulated Daoy-TrkA cells.…”
Section: Discussioncontrasting
confidence: 98%
“…The ability of DNRab5 to block NGF-induced macropinosomes is consistent with its known roles in mediating the early fusion of endosomes (15) and H-Ras-induced macropinosomes (49). With respect to DNRac1, as stated earlier, CA-Ras-dependent activation of macropinocytosis in U251 cells increased the pool of active Rac1 (21,23), which is known to serve a role in membrane ruffling and the formation of lamellipodia (50,51,52). In contrast, we found that the levels of NGF-activated Rac1 in Daoy-TrkA cells were relatively low by 12 to 24 h (Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…In GIT-PIXdependent systems, elevated Rac1 and/or Cdc42 activity has been found to be associated with reduced Arf6 activity (Albertinazzi et al, 2003;Hajdo-Milasinovic et al, 2009;Jones et al, 2009;Bhanot et al, 2010). However, a coordinated regulation, as opposed to merely a colocalization of GAP and GEF functions, has not been demonstrated.…”
Section: Git Proteinsmentioning
confidence: 99%